Perbedaan Perawatan Perineum Metode Sitz Bath Ekstrak Daun Pegagan (Centella Asiatica) dan Ekstrak Bunga Telang (Clitoria Ternatea) Terhadap Penyembuhan Luka Perineum Pada Ibu Postpartum - Ramadhanty, Shafira; Rahajeng Siti Nur Rahmawati; Susanti Pratamaningtyas; Indah Rahmaningtyas (JURNAL KEBIDANAN, 2024)
The puerperium is the time between the birth of the placenta and return of organs to their pre-pregnancy state. The postpartum period generally lasts 6-12 weeks after delivery. During the postpartum period, mothers need more attention, because as many as 50% of postpartum mothers experience tears in the birth canal. It is very important to do perineal care because the suture scars of the birth canal can be the entry point for germs and can cause infection. The purpose of this study was to determine the differences in perineal wound healing using the Sitz Bath method using Centella Asiatica leaf extract and butterfly pea flower extract (Clitoria Ternate) in Postpartum Mother. This research is a quantitative research with the type of pre-experimental research with the design of the research design used is the One Shoot Case Study design. The results of this study showed that perineal treatment using the sitz bath method using gotu kola leaf extract and pelang flower extract had a significant difference in perineal wound healing with a significance value (0.043 <0.05), The application of perineal care using the sitz bath method using gotu kola leaf extract and butterfly pea flower extract has been shown to be effective in healing perineal wounds. It is hoped that midwifery services need to develop postpartum care by applying several complementary therapies to help accelerate wound healing.